High platelet adrenergic activity and concomitant activation of the pituitary/medullar axis as alarming laboratory parameters in ACS survivors—the STRESS-AMI study - Gulyás, Zalán; Horváth, Zsófia; Hajtman, László; Kovács, Andrea; Kohut, László; Kósa, István; Tóth-Zsámboki, Emese; Kiss, Róbert Gábor (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Kinetics of stress-related biological parameters were determined in acute coronary syndrome (ACS) patients undergoing complex cardiovascular rehabilitation. Methods: We determined platelet functionality in the absence/presence of a selective alpha-2 adrenergic receptor inhibitor, atipemazole parallel with salivary cortisol levels at enrolment, and at 3- and 12-months follow-up in 75 ACS patients with percutaneous coronary intervention. Results: Pharmacological/non-pharmacological secondary prevention methods have been efficiently applied. Baseline aggregometry indicated platelet hyperactivity, decreasing gradually and being significantly reduced late, at 12 months (p<0.05). Cortisol levels followed similar kinetics (p<0.05). Baseline epinephrine-induced aggregations (EIA) significantly correlated with most of the other platelet agonists, even at subsequent time-points. Patients with upper-quartile EIA at enrolment (EIA-UQ) had significantly higher ADP- and collagen-induced aggregations at enrolment, at 3- and 12-months follow-up as well, indicating that high adrenergic response in the acute phase is accompanied by general platelet hyperactivity and predicts sustained platelet activation. In the EIA-UQ group higher cardiac biomarker release, elevated C-reactive protein and cortisol levels, and lower baseline left ventricular ejection fraction were detected. Atipemazole significantly reduced platelet aggregation induced by several platelet agonists, being most potent and comparable to full in vitro P2Y12 inhibition on collagen-induced aggregations (p<0.05), indicating that catecholamines might serve as promt/long-term modulators of platelet function. Discussion: Despite effective CCR programme and dual antiplatelet therapy, prolonged activation of sympathetic neuroendocrine system and general platelet hyperactivity can be detected up to one year in ACS patients with high adrenergic platelet activity. Moreover, initial high adrenergic activity is accompanied by clinical parameters associated to increased cardiovascular risk, therefore early identification of these patients might support complex optimal long-term therapy.